Spatial dynamics of the bearded goby and its key fish predators off Namibia vary with climate and oxygen availability. (March 2015) - Salvanes, Anne Gro V.; Bartholomae, Chris; Yemane, Dawit; Gibbons, Mark J.; Kainge, Paul; Krakstad, Jens‐Otto; Rouault, Mathieu; Staby, Arved; Sundby, Svein
Abstract: Hypoxia [O2 < 2.0 mL L −1 (87 μ mol kg −1 )] and severely hypoxic water masses [O2 < 0.5 mL L −1 (21.8 μ mol kg −1 )] are increasing in coastal marine ecosystems due to eutrophication and warming. Here, we investigate the response of the suboxic‐tolerant endemic fish, Sufflogobius bibarbatus, to variations in the thermal and oxygen environment, as well as to predation pressure, using 22 yr worth of satellite and in situ data. We show that environmental variation and predation pressure affect the goby population, which has expanded over the last decade while that of horse mackerel has contracted. These changes co‐occurred with a general warming in the north and central shelf areas (north of 24.5°S). Spring warming positively affected both goby and hake abundances, but not the horse mackerel, suggesting different responses to surface temperature. The goby habitat contracted when predators were abundant, particularly in the north, which is the fringe of its distributional area. The implications of the differential tolerance of gobies and their predators for climate variations are discussed.